Застосування eye tracking для управління системами з перебудованою структурою - Соколова, В. К. (ХНУРЕ, 2020)
There are many methods of automatic wheelchair management, but one or the other is not universal. Wheelchairs can be controlled with the help of voice, hands, and pulses of the cerebral cortex, but this is not always convenient. The paper proposes a new method of processing the image of the eye that enters the data processing system.
Keywords: eye-tracking